Cervical cancer screening in high-altitude areas in China: A large cross-section study of 25,173 women in northern Tibet - Wang, Qimin; He, Yingying; Long, Fang; Li, Chaoran; Shen, Zhuowei; Guo, Dongxing; Zhaxi, Duoji; Bumu, Lamu; Hua, Zhengyu; Sun, Zhigang; Jiang, Nan; Han, Xu; et al. (Frontiers in Oncology, 2022)
Background Cervical cancer has become a worldwide concern owing to its high incidence and mortality rates. To date, high-altitude areas of Tibet have not benefited from any large-scale cervical cancer screening programs. Therefore, we initiated a screening program to investigate the prevalence of human papilloma virus (HPV) and HPV genotype distribution to reveal cervical cancer and its precursor which lead to morbidity among women in the city of Nagqu in northern Tib3et. Methods A total of 25,173 women were recruited to undergo HPV genotype tests between June and December 2019. Women infected with HPV 16 and/or 18 underwent colposcopy and histological examination. Women with other high-risk HPV type (hr-HPV) underwent cytological tests to determine whether to conduct further colposcopy and histological examination for diagnosis. HPV prevalence was calculated in the total population and further stratified according to various parameters, such as age group, area location (altitude level), and single or mixed infection status. The HPV genotype distribution was also investigated accordingly. Cervical lesions revealed by further colposcopic findings were also analyzed; high-grade and malignant lesion morbidities were calculated in total and in each county. Most data were collected and analyzed using descriptive and consistency check statistical methods, and a risk factor investigation for HPV infection was performed using logistic regression models. Results The total HPV infection rate among women in Nagqu was 13.42%. Of the 25,173 women in the study, 999 (3.97%) were HPV 16/18 positive, 2,379 (9.45%) were other hr-HPV-positive, and 21,795 (86.58%) were HPV-negative. The five most common HPV genotypes, accounting for more than 60% of all HPV infections in Nagqu people, were HPV 16, 58, 31, 18, and 52. Tibetan women younger than 20 years and older than 60 years were the two age groups with the highest rates of HPV infection, 26.7% and 19.8%, respectively. Among the HPV-positive women, 2,656 (78.33%) were infected with a single strain and 732 (21.67%) were infected with multiple strains (more than two genotypes). HPV prevalence increased in high-altitude areas (positive rate highest in Nyima with an altitude of 5,000 m, 23.9%) and decreased in relatively low-altitude areas (positive rate lowest in Lhari with an altitude of 4,000 m, 6.6%). Multiple analyses showed that age, parity, age at first delivery, and altitude of residence were independent factors facilitating HPV infection in Tibetan women. High-grade and malignant cervical lesions revealed by histological findings were different among living locations, with the highest rates in Xainza, Baingoin, and Nyainrong, these being 2.019%, 1.820%, and 1.116%, respectively, among women in these areas. Conclusion Our survey provides an overall perspective on HPV genotype infection and cervical lesions in women in northern Tibet. The data not only provide useful information for the treatment of cervical lesions but also has great value in terms of the primary and secondary prevention measures that can be taken for women living in these regions. Clinical Trial Registration www.chictr.org.cn, indentifier ChiCTR2000035061.